A comparative study of two molecular mechanics models based on harmonic potentials - Zhao, J.; Wang, L.; Jiang, J.-W.; Wang, Z.; Guo, W.; Rabczuk, T.
We show that the two molecular mechanics models, the stick-spiral and the beam models, predict considerably different mechanical properties of materials based on energy equivalence. The difference between the two models is independent of the materials since all parameters of the beam model are obtained from the harmonic potentials. We demonstrate this difference for finite width graphene nanoribbons and a single polyethylene chain comparing results of the molecular dynamics (MD)simulations with harmonic potentials and the finite element method with the beam model. We also find that the difference strongly depends on the loading modes, chirality and width of the graphene nanoribbons, and it increases with decreasing width of the nanoribbons under pure bending condition. The maximum difference of the predicted mechanical properties using the two models can exceed 300 por ciento in different loading modes. Comparing the two models with the MD results of AIREBO potential, we find that the stick-spiral model overestimates and the beam model underestimates the mechanical properties in narrow armchair graphene nanoribbons under pure bending condition.
Keywords: ARMCHAIR GRAPHENE NANORIBBONS; BEAM MODEL; COMPARATIVE STUDIES; ENERGY EQUIVALENCE; FINITE WIDTH; GRAPHENE NANORIBBONS; HARMONIC POTENTIAL; LOADING MODES; MECHANICAL PROPERTIES OF MATERIALS; MOLECULAR DYNAMICS SIMULATIONS; POLYETHYLENE CHAINS; PURE BENDING